Antenatal counseling to ensure the quality of life of toddlers to be free from stunting towards a golden Indonesia in 2045 - Wangsanata, Susana Aditiya; Kibtyah, Maryatul; Rahayu, Sucik; Lukman Khakim, Ahmad; Andres Sanjaya, Lari; Jauro, Alfa (Journal of Advanced Guidance and Counseling, 2024)
Purpose –  The purpose of this study was to determine the impact of antenatal counseling on the quality of life of toddlers in order to realize the golden generation in 2045 in Indonesia. Method - This research method is library research, which is collecting various library data to solve stunting problems in Indonesia. Data collection techniques are collecting and identifying documents, reading and analyzing documents, synthesis and analysis, then drawing conclusions. The data analysis technique uses content analysis, which is an in-depth discussion of the contents of written information on the data that has been collected.. Result - The results of this study found that antenatal counseling can be an alternative solution to the problem of stunting in Indonesia. This is proven by several indicators, including, during antenatal counseling, pregnant women gain insight into PHBS during pregnancy. With PHBS insight, it can guarantee the quality of life during pregnancy and post-pregnancy. By maintaining PHBS during pregnancy and post-pregnancy, it can minimize toddler infections that interfere with digestion, causing nutritional failure and resulting in stunting.  Implication –  Antenatal counseling has an impact on the insight of pregnant women about the procedures for Clean and Healthy Lifestyle (PHBS) during pregnancy and post-pregnancy. By knowing the insight of PHBS, it can prevent infections in toddlers so that it can guarantee a good quality of life. Originality – Antenatal counseling provides knowledge for pregnant women on how to maintain physical and mental condition during pregnancy. This research is a research that has never been published in any form. *** Tujuan - Tujuan dari penelitian ini adalah untuk mengetahui dampak konseling antenatal terhadap kualitas hidup balita dalam rangka mewujudkan generasi emas pada tahun 2045 di Indonesia. Metode - Metode penelitian ini adalah penelitian kepustakaan, yaitu mengumpulkan berbagai data kepustakaan untuk memecahkan masalah stunting di Indonesia. Teknik pengumpulan data dengan mengumpulkan dan mengidentifikasi dokumen, membaca dan menganalisis dokumen, sintesis dan analisis, kemudian menarik kesimpulan. Teknik analisis data menggunakan analisis isi, yaitu pembahasan mendalam terhadap isi suatu informasi tertulis atas data yang telah dikumpulkan. Hasil - Hasil penelitian ini menemukan bahwa konseling antenatal dapat menjadi salah satu alternatif solusi bagi permasalahan stunting di Indonesia. Hal ini dibuktikan dengan beberapa indikator, diantaranya, pada saat konseling antenatal, ibu hamil mendapatkan wawasan tentang PHBS selama kehamilan. Dengan adanya wawasan PHBS, maka dapat menjamin kualitas hidup selama kehamilan dan pasca kehamilan. Dengan menjaga PHBS selama kehamilan dan pasca kehamilan, dapat meminimalisir infeksi balita yang mengganggu pencernaan sehingga menyebabkan gagal gizi dan mengakibatkan stunting.  Implikasi - Konseling antenatal berdampak pada wawasan ibu hamil tentang tata cara Perilaku Hidup Bersih dan Sehat (PHBS) selama kehamilan dan pasca kehamilan. Dengan mengetahui wawasan PHBS, maka dapat mencegah terjadinya infeksi pada balita sehingga dapat menjamin kualitas hidup yang baik. Keaslian - Konseling antenatal memberikan pengetahuan kepada ibu hamil tentang bagaimana menjaga kondisi fisik dan mental selama kehamilan. Penelitian ini merupakan penelitian yang belum pernah dipublikasikan dalam bentuk apapun.